2019
DOI: 10.24911/ijmdc.51-1573214220
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency among Type 2 Diabetes patients in Saudi Arabia: a systematic review

Abstract: Type 2 Diabetes mellitus (T2DM) is a metabolic disorder that represents a global health problem; its prevalence is increasing globally. Saudi Arabia is having one of the highest prevalence of T2DM in the world. Vitamin D is important for the health of bone; its deficiency is associated with increased vascular complications in patients with T2DM. The current systematic review was aimed at exploring the association between vitamin D and T2DM. This study included all the studies which focused and reported the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Untreated T2DM can lead to several comorbidities, including micro-and macro-vascular complications. One of the major risk factors for CAD is diabetes mellitus (30,1). HIFs have a role in the progression of β cell dysfunction and diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untreated T2DM can lead to several comorbidities, including micro-and macro-vascular complications. One of the major risk factors for CAD is diabetes mellitus (30,1). HIFs have a role in the progression of β cell dysfunction and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence has increased dramatically in developing countries. The number of people with T2DM is projected to more than double by 2030, reaching 366 million people worldwide (1). The prevalence of diabetes in Saudi Arabia is the second highest in all of the Middle Eastern countries and ranks seventh worldwide (2).…”
mentioning
confidence: 99%
“… 18 The probability of developing T2DM was substantially high in both males and females and it has been suggested that 25-OH D deficiency might contribute to T2DM development. 19 Vitamin D deficiency is suggested to be one of the factors that influence many processes involved in T2DM. 20 Vitamin B12 deficiency-associated peripheral neuropathy can also remain subclinical and interact with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, its prevalence has risen considerably. By 2030, the number of persons with T2DM is expected to be more than doubled, with 366 million people worldwide (1).…”
mentioning
confidence: 99%
“…According to a study conducted to discover the association between 25-OH D and T2DM, the probability of developing T2DM was substantially lower in both sexes (40-74 years of age) in the case of highest serum 25-OH D as matched to the lowest level. It has been proposed that 25-OH D deficiency might contribute to T2DM development (1). 25-OH D is considered to affect CAD through a variety of processes, including carbohydrate and fat metabolic abnormalities.…”
mentioning
confidence: 99%